Is Troponin really a reliable marker in patients with acute ischemic stroke? - Yildiz Zeynep; Koçer Abdulkadir; Avşar Şahin; Cinier Göksel (Sciendo, 2018)
Background and purpose. Cardiac troponin I (cTnI) is a reliable marker to diagnose acute myocardial infarction, but the pathophysiological explanation for the increase in cTnI levels in patients with acute ischemic stroke (IS) remains unknown. To overcome this question, we aimed to compare serum cTnI levels in acute coronary syndrome (ACS) concomitant with and without stroke. By doing like this, we thought that we could demonstrate the effect of stroke on TrpI level. Methods. Serum cTnI levels of 41 patients having ACS with acute IS during hospitalization were compared with 97 control patients having only ACS. Cranial CT was performed to evaluate the lesions. The severity of IS was evaluated objectively by national institutes of health stroke scale. Results. cTnI levels were found to be similar in both groups. Presence of diabetes mellitus, coronary artery disease and previous myocardial infarction were more frequent in patients with acute IS. The cTnI levels in the patients with the cranial lesion in the anterior circulation was higher (p = 0.039). Presence of acute IS, cTnI level higher than 20 ng/mL and left ventricular ejection fraction < 40% were found to be independent risk factors for mortality (p < 0.05). Conclusions. We found that abnormal troponin levels were more likely to be due to cardiac causes than cerebral ones in this first study evaluating the cTnI levels in patients with ACS concomitant with acute IS. The severity of IS, lesion location in the anterior circulation and higher troponin levels were associated with mortality.